Seroprevalence of Neospora caninum in a dairy herd in Boyacá, Colombia - Pulido-Medellín, Martín Orlando (2016)
The aim of the present study was to determine the presence of antibodies against Neospora caninum in a dairy herd in the municipality of Toca, Colombia. Blood samples (n=100) were collected from females between 1 and 9 years of age. The animals were selected through simple random method of prospective cross-cut. The serum samples were processed using a commercial indirect ELISA kit. The prevalence of antibodies anti-N. caninum was 64%. The association between positive animals with history of abortion and parity was statistically significant (p<0.05), while the association with age, reproductive status and repeat breeding was not significant.